Design of Interrogation Protocols for Radiation Dose Measurements Using Optically-Stimulated Luminescent Dosimeters. Issue 3 (March 2017) - Abraham, Sara A.; Kearfott, Kimberlee J.; Jawad, Ali H.; Boria, Andrew J.; Buth, Tobias J.; Dawson, Alexander S.; Eng, Sheldon C.; Frank, Samuel J.; Green, Crystal A.; Jacobs, Mitchell L.; Liu, Kevin; Miklos, Joseph A.; et al.
Abstract : Abstract: Optically-stimulated luminescent dosimeters are capable of being interrogated multiple times post-irradiation. Each interrogation removes a fraction of the signal stored within the optically-stimulated luminescent dosimeter. This signal loss must be corrected to avoid systematic errors in estimating the average signal of a series of optically-stimulated luminescent dosimeter interrogations and requires a minimum number of consecutive readings to determine an average signal that is within a desired accuracy of the true signal with a desired statistical confidence. This paper establishes a technical basis for determining the required number of readings for a particular application of these dosimeters when using certain OSL dosimetry systems.